Twelve tips for teaching quality improvement in the clinical environment. (3rd October 2018) - Narayanan, Maya; White, Andrew A.; Gallagher, Thomas H.; Mookherjee, Somnath
Abstract: Medical educators are expected to teach quality improvement (QI) skills alongside traditional clinical skills such as physical examination and bedside manner. Educational resources for intensive training in QI have proliferated. However, many physicians lack the time or resources to undergo this training, and may struggle with teaching these skills to their learners. In response, we offer twelve tips to help physicians teach basic QI concepts in the clinical environment. By following these tips physicians will be able to engage their learners interest in QI and provide experiential learning that makes a lasting impact.